2008
DOI: 10.1111/j.1539-6924.2008.01069.x
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Risk Perception Study of Attitudes Toward Homeland Security Systems

Abstract: Understanding the issues surrounding public acceptance of homeland security systems is important for balancing security needs and potential civil liberties infringements. A psychometric survey was used in an exploratory study of attitudes regarding homeland security systems. Psychometric rating data were obtained from 182 respondents on psychological attributes associated with 12 distinct types of homeland security systems. An inverse relationship was observed for the overall rating attributes of acceptability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 10 publications
4
35
0
Order By: Relevance
“…However, there is disagreement regarding the effectiveness of media communication as an effective influencing factor. Clothier et al (2015), Moussaïd, M. (2013) and Sanquist et al (2008) concluded that the media could be a significant influencing factor. Sjöberg (2000) differed concluding it was not as significant as other influencing factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is disagreement regarding the effectiveness of media communication as an effective influencing factor. Clothier et al (2015), Moussaïd, M. (2013) and Sanquist et al (2008) concluded that the media could be a significant influencing factor. Sjöberg (2000) differed concluding it was not as significant as other influencing factors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, nuclear war images negatively affected perceived risk regarding nuclear power (Slovic et al, 1991). Clothier et al (2015) and Sanquist et al (2008) found that media communication can be very influential in forming perceived risk opinions, especially when there is little subject knowledge. Moussaïd (2013) supports this premise stating that individuals often seek media information to fill knowledge gaps with the amount dictated by existing knowledge.…”
Section: Media Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Where research has considered how people relate to, embrace, or reject, identity management technologies (IMTs) in everyday life (e.g. Byun & Byun, 2013;Clodfelter, 2010;Hossain & Prybutok, 2008;James, Pirim, Boswell, Reithel, & Barkhi, 2006;Sanquist, Mahy, & Morris, 2008;Smith, 2008), it has typically assumed the citizen or the consumer to be a rational actor, making instrumental choices on the basis of perceived usefulness and efficiency. To do so, though, ignores the cultural narratives that precede and interact with the technologies and the ways in which they are understood.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that members of the public, in general, struggle to understand the science behind cybercrime and cybersecurity and this problem is exacerbated by the different regulatory frameworks associated with cybercrime, thereby resulting in a confusing array of issues for the average citizen [41]. One key issue in setting-up an effective and robust evidence-chain that might lead to successful prosecution in the cloud crime arena concerns the way in which the underlying crimes may be communicated to key stakeholders and to the general public.…”
Section: The Importance Of Crime Scriptsmentioning
confidence: 99%